2023
DOI: 10.3390/ijms24087284
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Fibroblast Growth Factor-21: A Systematic Review and Meta-Analysis

Abstract: This systematic review aimed to synthesize and quantify the results of the studies investigating the changes in fibroblast growth factor-21 (FGF-21) induced by exercise. We searched for studies that did not differentiate between patients and healthy adults but compared them before and after exercise and with and without exercise. For quality assessment, the risk-of-bias assessment tool for nonrandomized studies and the Cochrane risk-of-bias tool were used. A quantitative analysis was performed using the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The FGF and FGFR (fibroblast growth factor receptor) signaling systems regulate exercise-induced cardiac hypertrophy. 59 However, current research has primarily focused on FGF2 60 and FGF21, 61 neglecting FGF5. Furthermore, large prospective studies are needed to investigate the role of FGF5.…”
Section: Discussionmentioning
confidence: 99%
“…The FGF and FGFR (fibroblast growth factor receptor) signaling systems regulate exercise-induced cardiac hypertrophy. 59 However, current research has primarily focused on FGF2 60 and FGF21, 61 neglecting FGF5. Furthermore, large prospective studies are needed to investigate the role of FGF5.…”
Section: Discussionmentioning
confidence: 99%
“…Through PPARg-mediated transcriptional activation, exercise induces adipose expression of FGFR1 and bklotho, sensitizing FGF21 actions in adipose tissues to send humoral signals for multi-organ crosstalk, thereby maintaining metabolic homeostasis (80). A systematic review, involving 376 participants from 10 studies, demonstrated a significant increase in FGF-21 levels after exercise compared to no exercise (81). Longterm aerobic exercise has been observed to lower human FGF21 levels and is associated with an improvement in FGF21 resistance (34).…”
Section: Fgf21 Is a Potential Target For Dkd Therapymentioning
confidence: 99%
“…Promotes Fiber-Type Remodeling, Inhibits TGF-β1-Smad2/3-mmp9, and Activates p38 MAPK Signaling Pathway in C2C12 Myotubes Fgf21, primarily secreted by the liver and also produced in other tissues including muscle, is known to enhance the function of mitochondria, the cellular components responsible for energy production, potentially impacting muscle fiber type indirectly [25,26]. To investigate the direct role of Fgf21 in regulating muscle fiber types, we performed immunoblot analysis of MyHC I, MyHC IIa, MyHC IIb, TGF-β1, Smad2/3, mmp2, mmp9, and p-p38 proteins in C2C12 cells.…”
Section: Fgf21mentioning
confidence: 99%